Effect of Revalor-G on the performance of stocker heifers grazing irrigated, smooth bromegrass pasture for a full season - Kuhl, Gerry L.; Reynolds, M.D.; Brandt, Robert T., Jr.; Blasi, Dale A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 150-day field study was conducted to evaluate single vs. reimplant strategies for stocker heifers grazing irrigated smooth bromegrass . Three hundred forty-three previously nonimplanted British crossbred heifers averaging 494 lb were assigned to one of seven treatments: 1) no implant-control (NC), 2) Revalor-G® (REVG), 3) Ralgro® (RAL), 4) Synovex-H® (SYNH), 5) REVG/REVG, 6) RAL/RAL, and 7) SYNH/SYNH. Reimplanting (Treatments 5, 6 , and 7) was done on day 75 of the trial. In the first 75 days, all implants increased (P<.05) average daily gain (ADG) compared to NC. For the last 75 days (days 75 through 150), heifers implanted with REVG, REVG/REVG, RAL/RAL, and SYNH gained faster (P<.05) than NC or those implanted with RAL, and SYNH/SYNH. No significant differences occur red among the latter three treatments. Over the entire trial, there was no advantage to reimplanting heifers with REVG or RAL. SYNH/ SYNH heifers gained less (P<.05) than their single -implanted counterparts.
Keywords: Beef; Growth implant; Revalor-G; Ralgro; Synovex; Heifers; Pasture